2021
DOI: 10.3390/cancers13092246
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diffuse Liver Diseases on the Occurrence of Liver Metastases in Cancer Patients: A Systematic Review and Meta-Analysis

Abstract: This systematic review with meta-analysis aimed to assess the effect of diffuse liver diseases (DLD) on the risk of synchronous (S-) or metachronous (M-) liver metastases (LMs) in patients with solid neoplasms. Relevant databases were searched for systematic reviews and cross-sectional or cohort studies published since 1990 comparing the risk of LMs in patients with and without DLD (steatosis, viral hepatitis, cirrhosis, fibrosis) in non-liver solid cancer patients. Outcomes were prevalence of S-LMs, cumulativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…a higher frequency of hepatic steatosis in patients with higher BMIs, an expected finding, we found no association between hepatic steatosis and any of the evaluated tumor or patient characteristics. Despite studies in other solid tumors, 18,29,30 mostly in the colorectal cancer population, there are (to our knowledge) only 2 previously published studies (both retrospective) addressing a similar question in a population of patients with breast cancer. Duran et al 16 evaluated hepatic steatosis with CT in 107 consecutive patients with metastatic breast cancer and found the frequency of hepatic metastases was significantly higher in patients with hepatic steatosis (46.4% vs 22.8%, P = .018).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…a higher frequency of hepatic steatosis in patients with higher BMIs, an expected finding, we found no association between hepatic steatosis and any of the evaluated tumor or patient characteristics. Despite studies in other solid tumors, 18,29,30 mostly in the colorectal cancer population, there are (to our knowledge) only 2 previously published studies (both retrospective) addressing a similar question in a population of patients with breast cancer. Duran et al 16 evaluated hepatic steatosis with CT in 107 consecutive patients with metastatic breast cancer and found the frequency of hepatic metastases was significantly higher in patients with hepatic steatosis (46.4% vs 22.8%, P = .018).…”
Section: Discussionmentioning
confidence: 96%
“…Conflicting results concerning the effects of hepatic steatosis on the incidence of liver metastases are not unique to breast cancer but rather have been reported for multiple other solid tumor types as well. 18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study, the OS for stage 0‐II was 66.3% and 45.5% for stage III‐IV [21]. It is postulated that the diseased liver maybe protective against liver metastases as it is a hostile environment for the liver metastasis to occur due to the complex interplay between the tumour and host cells that modifies the liver microenvironment [39]. Han et al demonstrated that lungs were the common site of metastasis in liver cirrhosis patients as compared to the liver in the non‐cirrhosis group [22].…”
Section: Discussionmentioning
confidence: 99%
“…zelluläres Karzinom (HCC) handelt, sehr groß [51,52]. Während Patienten mit Leberzirrhose auch häufiger ein intrahepatisches Cholangiokarzinom entwickeln als die Normalbevölkerung, werden Metastasen nur selten in einer zirrhotischen Leber angetroffen [53]. Sie sind jedoch die häufigsten malignen Läsionen in der nicht-zirrhotischen Leber.…”
Section: Merkeunclassified